1972
DOI: 10.1111/j.1399-3054.1972.tb03589.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses of Apple Trees to Supraoptimal Root Temperature

Abstract: Ungrafted apple rootstocks were grown in sand cultures at constant root temperatures between 20°C to 40°C. Temperatures of 30°C and above reduced root and shoot growth. Serious damage to the leaves occurred at 35°C and above. The O2 consumption, CO2 evolution and respiratory quotient (RQ) of the roots showed maximum values at 35°C. Different rootstock cultivars varied greatly in their susceptibility to damage by supraoptimal root temperatures apparently due to anaerobic respiration. The more susceptible ones d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…), and apple trees (Malus sylvestris Mill. ), supraoptimal root temperature caused negative effects on shoot and root growth (Du and Tachibana, 1994a;Gur,et al, 1972;Lyons et al, 2007;Xu and Huang, 2000a), photosynthesis and carbohydrate metabolism (Du and Tachibana, 1994b;Xu and Huang, 2000b), and water and nutrient uptake (Huang and Xu, 2000;Klock et al, 1997;Tahir et al, 2008). The production of cytokinins and abscisic acid (ABA) in roots has been suggested to have a significant role in regulating shoot growth and photosynthesis under high soil temperature in wheat and grass (Liu and Huang, 2005).…”
mentioning
confidence: 99%
“…), and apple trees (Malus sylvestris Mill. ), supraoptimal root temperature caused negative effects on shoot and root growth (Du and Tachibana, 1994a;Gur,et al, 1972;Lyons et al, 2007;Xu and Huang, 2000a), photosynthesis and carbohydrate metabolism (Du and Tachibana, 1994b;Xu and Huang, 2000b), and water and nutrient uptake (Huang and Xu, 2000;Klock et al, 1997;Tahir et al, 2008). The production of cytokinins and abscisic acid (ABA) in roots has been suggested to have a significant role in regulating shoot growth and photosynthesis under high soil temperature in wheat and grass (Liu and Huang, 2005).…”
mentioning
confidence: 99%
“…6). Gur et al (1972) reported that the optimum root-zone temperature for apple growth was between 18 and 25°C. Temperatures higher than 30°C were growth limiting.…”
Section: Resultsmentioning
confidence: 99%
“…A 10 • C rise would have a proportionally even greater effect than the expected doubling of the temperature gradient. In addition to this direct effect of temperature on evaporation, it may further increase transpiration by maintaining the stomata open due to increased root temperature (Gur et al, 1972). The danger of drought injury under such conditions is obviously great, even without a deficiency in soil moisture.…”
Section: High Temperature Stressmentioning
confidence: 99%